2020
DOI: 10.1186/s10194-020-01118-1
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted functional connectivity between sub-regions in the sensorimotor areas and cortex in migraine without aura

Abstract: Background: Migraine is a severe and disabling brain disorder, and the exact neurological mechanisms remain unclear. Migraineurs have altered pain perception, and headache attacks disrupt their sensory information processing and sensorimotor integration. The altered functional connectivity of sub-regions of sensorimotor brain areas with other brain cortex associated with migraine needs further investigation. Methods: Forty-eight migraineurs without aura during the interictal phase and 48 age-and sex-matched he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Interestingly, the same technique also showed a heightened connection between sensory areas and areas regulating affective processes including the limbic system [ 25 28 ], which is implied in pain processing and in the regulation of emotional life. This may explain migraineurs’ susceptibility to external triggers causing sensory overload; those triggers may modify brain circuits functioning [ 29 31 ]. Individuals with migraine show a decreased threshold for several sensory stimuli, including sensory, pain, thermal, visual, auditory, and olfactory ones, which well correlates with the symptoms of increased sensitivity to light, noise, and odors reported by migraineurs not only during, but also between their attacks.…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…Interestingly, the same technique also showed a heightened connection between sensory areas and areas regulating affective processes including the limbic system [ 25 28 ], which is implied in pain processing and in the regulation of emotional life. This may explain migraineurs’ susceptibility to external triggers causing sensory overload; those triggers may modify brain circuits functioning [ 29 31 ]. Individuals with migraine show a decreased threshold for several sensory stimuli, including sensory, pain, thermal, visual, auditory, and olfactory ones, which well correlates with the symptoms of increased sensitivity to light, noise, and odors reported by migraineurs not only during, but also between their attacks.…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…In particular, focusing on the intricacy of aura presentation, whilst the majority of MwA patients exclusively experience visual symptoms, a minority of patients report, along with visual phenomena, also somatosensory or dysphasic symptoms representing the so‐called ‘complex aura’ [ 3 ]. In the latter, visual, somatosensory and dysphasic symptoms follow one another, usually beginning with visual, then somatosensory and finally motor or aphasic manifestations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These GM regions are believed to play critical roles in the pathophysiology of migraines. Our previous study indicated disrupted functional connectivity between the thalamus, sensorimotor areas, posterior pons, and other migraine-relevant brain regions in MWoA patients ( Qin et al, 2020a , b , c ). We speculated that the disrupted functional connections of the cortical regions in migraine patients may be due to the abnormal functional coupling between GM regions and WM regions.…”
Section: Discussionmentioning
confidence: 94%